Molecular imaging of tumors with nanobodies and antibodies: Timing and dosage are crucial factors for improved in vivo detection. (27th April 2015) - Bannas, Peter; Lenz, Alexander; Kunick, Valentin; Well, Lennart; Fumey, William; Rissiek, Björn; Haag, Friedrich; Schmid, Joanna; Schütze, Kerstin; Eichhoff, Anna; Trepel, Martin; Adam, Gerhard; et al.
<x xml:space="preserve">Abstract</x> The utility of nanobodies and conventional antibodies for in vivo imaging is well known, but optimum dosing and timing schedules for one versus the other have not been established. We aimed to improve specific tumor imaging in vivo with nanobodies and conventional antibodies using near‐infrared fluorescence (NIRF) imaging. We used ARTC2 expressed on lymphoma cells as a model target antigen. ARTC2‐specific nanobody s+16a and conventional antibody Nika102 were labeled with NIRF‐dye AF680. In vivo NIRF‐imaging of ARTC2‐positive and ARTC2‐negative xenografts was performed over 24 h post‐injection of 5, 10, 25, or 50 µg of each conjugate. Specific target‐binding and tissue‐penetration were verified by NIRF imaging ex vivo, flow cytometry and fluorescence microscopy. NIRF‐imaging of s+16a680in vivo revealed a six times faster tumor accumulation than of Nika102680. Using 50 µg of s+16a680 increased the specific signals of ARTC2‐positive tumors without increasing background signals, allowing a tumor‐to‐background (T/B) ratio of 12.4 ± 4.2 within 6 h post‐injection. Fifty micrograms of Nika102680 increased specific signals of ARTC2‐positive tumors but also of ARTC2‐negative tumors and background, thereby limiting the T/B ratio to 6.1 ± 2.0. Ten micrograms of Nika102680 only slightly reduced specific tumor signals but dramatically reduced background signals. Ex vivo analyses confirmed a faster and deeper tumor penetration with s+16a680. Using nanobody s+16a allowed same‐day imaging with a high T/B ratio, whereas antibody Nika102 gave optimal imaging results only 24 h post injection. Nanobody s+16a required a high dose, whereas antibody Nika102 had the best T/B‐ratio at a low dose. Therefore, timing and dosage should be addressed when comparing nanobodies and conventional antibodies for molecular imaging purposes. Copyright © 2015 John Wiley & Sons, Ltd.